PENGUATAN SKILL CALON WIRAUSAHA DAWIS DALAM PRODUKSI & DIFERSIFIKASI KULINER BERBAHAN BAKU MBOTHE MENGGUNAKANTEKNOLOGI AGRO MANUFACTURING - Ronny Hendra Hertanto; Achmad Dahlan (Publisher UPT P2M Politeknik Negeri Malang, 2017)
This lbM implementation program is carried out in line with the Agro Manufacturing Skill transfer to the entrepreneur DAWIS candidates. This program will enable them to process raw Taro to become Taro Nudle, Taro Brouwnies, Taro Bakpao, Taro Dougnut as to avoid crop leftovers. When they have the skill, it is hoped that they can initiate the business independently, in which it will create business opportunities in agricultural people sector. Besides, they will be equipped with managing financial administration skill that it includes marketing aspects. This, in turns, may initiate PIRT (legal home industries) so that their products can be placed in formal markets such as mini markets and supermarkets.